Harvesting microalgae, Chlorella sp. by bio-flocculation of Moringa oleifera seed derivatives from aquaculture wastewater phytoremediation - Azizah, Endut; Siti Hajar, Abdul Hamid; Fathurrahman, Lananan (2014)
Moringa oleifera (MO) seed has been widely used for water treatment purposes due to their good ﬂocculation, low cost and non-toxic characteristics. However, these advantages had not yet been utilized for the microalgae harvesting technology. Until today, the harvesting of microalgae biomass still depend on sophisticated and complex approaches such as hollow ﬁber ﬁltration, chemical ﬂocculants and Alfa Laval decanter technology. Thus, in this study the potential of natural plant-based coagulant was investigated.MO seed derivatives were determined for the harvesting of suspended freshwater microalgae, Chlorella sp.. Flocculation characteristics with various dosages were optimized. The output of this study proved that primary and tertiary MO derivatives yield excellent ﬂocculation efﬁciency of more than 95% at20 min sedimentation. In fact, MO derivatives even supersede chemical ﬂocculants, Aluminum Sulfate in terms of ﬂocculation efﬁciency and biomass recovery at a low dosage of 10 mg L1and normal pH (6.9e7.5). Seed powder had the highest removal efﬁciency whereas seed protein had the highest biomass recovery. Utilization of M. oleifera derivatives as bio-coagulant provides several advantages such as lower impact on the environment, lower cost for microalgae harvesting, allow rapid microalgae culture expansion and as chemical-free green technology.